Are You Creative? What College-Level English Language Learners Think of AI Writing Assistants - Syabilla, Zalsa Febrina; Romadhon, M. Galuh Elga; Mustofa, Mutmainnah (VELES Voices of English Language Education Society, 2023)
This study explores the perspectives and experiences related to AI writing assistants for college-level English language learners, casting light on potential as valuable supports for language learning and academic writing enhancement. This study uses a qualitative design with narrative inquiry approach. The study was conducted with three English Language Learners in Magister program from one university in Malang. The two research questions were addressed by conducting semi-structured interviews with these students. The results of this investigation show that students' perceptions of ChatGPT were contradictory, with both positive and negative aspects swaying their perspectives. Moreover, the study highlighted factors among them academic workload, time efficiency, and affordability that affected the English language learner’s intent to employ ChatGPT as a writing assistant in an academic context. Regardless the numerous benefit such as instant feedback, grammar proofreading correction, expanding vocabulary, and language style suggestions, the incorporation of AI-based writing aids in academic contexts still faces ethical and practical challenges. Gaining a comprehensive understanding of these aspects can provide valuable insights for educators, enabling them to develop efficacious strategies for the responsible and sustainable integration of AI tools. These strategies aim to effectively facilitate language learning and academic writing for those who are learning English as a foreign language.